Market Development and the Asset Growth Effect: International Evidence - Titman, Sheridan; John Wei, K. C.; Xie, Feixue (Journal of Financial and Quantitative Analysis, 2013)
Abstract A number of studies of U.S. stock returns document what is referred to as the investment or asset growth effect. Specifically, firms that increase investment or total assets subsequently earn lower risk-adjusted returns. This study finds substantial cross-country differences in the asset growth effect. In particular, the asset growth effect is stronger in countries with more developed financial markets, but it does not seem to be associated with corporate governance or the costs of trading. Overall, the evidence is consistent with a q-theory where financial market development captures either managers’ willingness or ability to align investment expenditures to the cost of capital, but it is inconsistent with the hypothesis that the asset growth effect is due to bad governance and overinvestment.